Modeling the Impact of Pandemic-Induced Shocks and Support Measures with an Emerging Market Economy: A GUI-Model Approach - Parvez, Md. Al-Amin; Shaeba, Mashrura Kabir; Hossain, Md. Sajjad; Katha, Evanta Hashem (Finance & Economics Review, 2022)
Purpose: This paper analyzes the impacts of COVID-19 shocks on an emerging market economy using a Graphical User Interface (GUI) model. Methods: Event study analysis has been adopted using secondary data for measuring the impacts and impulse responses of different shocks. Results: The paper shows how the shocks affect the economy using graphical presentations of impulse responses of major macroeconomic indicators. The shapes and movements of the impulse response curves indicate how the effects pass through from one sector to another; how long the effects may persist in the economy, and how much time will be required for recovery. All these simulations suggest that immediate supportive measures from both fiscal and monetary sides help recover the economy, although marginally due to the required higher costs stemming mainly from the higher exchange rate volatility. Implications: Several policy implications such as sector-specific support measures, prioritization of sectors, rationing of credit facilities, efficient exchange rate management, etc., can be followed by the countries regarding fiscal and monetary policy measures towards reducing COVID-19-induced similar shocks.